Right of Access to Legal Aid for the Poor: Study of Islamic Civil Cases in the PA Ponorogo Legal Area - Arliana Agustin Faridhatul Shima; Lukman Santoso (Faculty of Sharia, Institut Agama Islam Negeri (IAIN) Metro, Lampung, Indonesia., 2024)
Pro bono legal aid must be provided by Advocates to underprivileged people, as written in Article 22 Paragraph 1 of Law No. 18 of 2003 concerning Advocates. Pro bono assistance is provided to fulfill access to justice. The high poverty rate in Ponorogo Regency and the limited amount of pro bono assistance provided each year make it difficult for underprivileged people to access and obtain legal aid, because not all advocates have carried out their obligations to provide pro bono assistance at the Ponorogo Religious Court . This research is a qualitative research with empirical legal research type. Data collection techniques using snowball sampling. The analysis method uses qualitative analysis. From this research it can be concluded that first, each advocate has its own criteria, namely that the client pays the costs of the case because the Advocate only provides free legal aid services and the Court has no special budget for pro bono assistance. Although they have their own criteria, the assistance has fulfilled the values of justice, helping and Maqāshid al-Sharī'ah , namely the protection of the soul. Second, the process of providing pro bono assistance has not been carried out optimally because not all advocates have fulfilled their obligations to provide pro bono assistance. Although it has not been done optimally, it has fulfilled the principles of Islamic law, namely the value of tolerance, Amar Ma'ruf Nahi Munkar, equality and Maqāshid al-Syarī'ah on the protection of offspring and property.